Social, Cognitive, Teaching, and Technology Presence in Blended Inquiry Learning: A Higher Education Study - Bambang Riadi; Muhammad Fuad; Dwi Yulianti; Rangga Firdaus (Online Learning In Educational Research (OLER), 2024)
Blended Inquiry Learning (BIL), an approach integrating blended and inquiry-based methods, seeks to enhance higher-order thinking skills (HOTS), including analysis, evaluation, and creation. This study explores the impact of BIL by assessing the roles of social, cognitive, instructional, and technological presence. Employing quantitative methods, data were gathered using a 19-item Likert scale questionnaire and analyzed through Partial Least Squares (PLS) Regression, a structural equation modeling technique. Participants included 222 students from various departments enrolled in the Indonesian Language Education course at the University of Lampung. The findings indicate that all four presences significantly influence BIL effectiveness, with technological presence having the most substantial effect and social presence the least. The study further advocates for incorporating technological presence as a fundamental component in the Community of Inquiry (CoI) framework to enhance the integration of digital technologies in education. This revised framework enables educators to design learning experiences that align with the demands of the technological era, utilizing tools such as Learning Management Systems (LMS), computer-based simulations, and virtual collaboration platforms